Utilization of Industrial Waste for the Production of Environmentally Friendly Briquettes as a Solution to Supporting the Green Industry - Irwan, Muhammad; Sitanggang, Boy Chandra (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2025)
The food and beverage industry in Indonesia generates solid waste such as tea residues, Fly Ash and Bottom Ash (FABA) from palm kernel shells, wood pallet sawdust, and cardboard, which pose a risk of environmental pollution. Utilizing this waste as briquettes offers an innovative solution to reduce pollution while supporting the Green Industry program launched by the Indonesian Ministry of Industry. Briquettes, as solid fuel made from organic materials, can replace coal, reduce carbon emissions, and provide environmental benefits. This study aims to develop methods for utilizing industrial waste to produce eco-friendly briquettes. Quality tests include measuring moisture content, ash content, volatile matter, and calorific value. The results indicate that tea residues and pallet sawdust have high calorific values of 5049.63 Kcal/Kg and 5053.71 Kcal/Kg, respectively, comparable to coal. Tea residues exhibit a high volatile matter content (43.80%) for efficient combustion, while pallet sawdust shows low ash content, improving efficiency. FABA is used as a filler material with a calorific value of 3648.81 Kcal/Kg and a volatile matter content of 85.43%, supporting combustion and increasing briquette mass. The combination of these materials produces environmentally friendly briquettes with competitive combustion performance. These waste-based briquettes hold great potential for application in the food and beverage industry, promoting sustainable waste management and achieving green industry targets.